1 Maintaining an impact agenda when study findings point in multiple directions. Perspectives on the Australian 3D case series study. (18th October 2022) - Laur, Celia; Burch, Emily; Williams, Lauren T; Ball, Lauren
Abstract : Background: Health research builds evidence to positively impact populations and health systems. However, at the conclusion of individual research projects, the findings may not always indicate a clear direction for pursuing positive impact. Type 2 Diabetes Mellitus (T2DM) is a lifestyle-related chronic disease, with the 2019 global prevalence estimated at 9.3% (463 million people). Objectives: Using the Australia 3D study as an example, this work discusses ways forward for researchers when study findings provide multiple options for population and health system impact, rather than one clear direction. Methods: The 3D longitudinal, case-series study of 225 adult Australians newly diagnosed with T2DM, focused on answering the question: How does Diet Change after Diagnosis with T2DM? All results are published separately, and this work synthesizes findings to plan next steps in pursuing meaningful impact. Results: Overall, the 3D study found that very few people newly diagnosed with T2DM make meaningful, sustained improvements to diet quality. However, no sociodemographic, health, or behavioural factors were identified as being consistently influential in supporting success in dietary changes. These results provide several options for next steps to support those newly diagnosed with T2DM. To have a tangible health system and population impact, results need to be considered within the wider context (i.e., sociodemographic, and cultural factors), and thus an implementation study is suggested. The next steps for 3D should also be collaborative, such as using an Integrated Knowledge Translation (IKT) approach, which involves knowledge users (i.e., those most impacted, such as patients, community partners, and health system stakeholders). In IKT, researchers and knowledge users work collaboratively to develop priorities and research questions, interpret findings, and put results into practice. Conclusion: Determining the next steps in any research program can be challenging. The 3D study began with lived-experience input and has advanced the evidence regarding diet quality for individuals recently diagnosed with T2DM. Next steps will be driven by a variety of factors, including funding and resources, researcher capacity, and community engagement.